2014
DOI: 10.1002/asl2.524
|View full text |Cite
|
Sign up to set email alerts
|

Towards an aerosol classification scheme for future EarthCARE lidar observations and implications for research needs

Abstract: Owing to the high variability of aerosols, and their different impact on the Earth's climate system, aerosol type classification from satellite measurements is of high importance. Polarization sensitive lidar measurements on board the future Earth Clouds, Aerosols and Radiation Explorer (EarthCARE) satellite mission will provide information to distinguish different aerosol types. We analyze whether former classification schemes based on lidar measurements at 532 nm are applicable to EarthCARE measurements at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
73
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 37 publications
12
73
0
Order By: Relevance
“…While the first properties give us information about the aerosol load, the latter two properties are intensive lidar properties and thus only dependent on the aerosol type and not on its amount. Therefore, these properties are used for aerosol classification schemes based on lidar measurements (Burton et al, 2012;Groß et al, 2013Groß et al, , 2015Illingworth et al, 2015). The measurements and results of this work follow up former measurements performed during the SAMUM-1 (Freudenthaler et al, 2009;Tesche et al, 2009b) and SAMUM-2 Tesche et al, 2011) campaigns and during a strong Saharan dust event over Central Europe observed in the framework of EARLINET (Wiegner et al, 2011).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…While the first properties give us information about the aerosol load, the latter two properties are intensive lidar properties and thus only dependent on the aerosol type and not on its amount. Therefore, these properties are used for aerosol classification schemes based on lidar measurements (Burton et al, 2012;Groß et al, 2013Groß et al, , 2015Illingworth et al, 2015). The measurements and results of this work follow up former measurements performed during the SAMUM-1 (Freudenthaler et al, 2009;Tesche et al, 2009b) and SAMUM-2 Tesche et al, 2011) campaigns and during a strong Saharan dust event over Central Europe observed in the framework of EARLINET (Wiegner et al, 2011).…”
Section: Discussionsupporting
confidence: 58%
“…With our measurements during the SALTRACE campaign, in combination with the findings of former measurements of fresh and mid-range transported dust during the SAMUM project and long-range transported dust measurements over Central Europe, we are now able to investigate the effect of transport and aging on the lidar optical properties of Saharan dust. Figure 14 shows the particle linear depolarization ratio versus the lidar ratio at 355 and 532 nm of the different aerosol types which are, until now, included in the aerosol classification schemes for EarthCARE (Illingworth et al, 2015;Groß et al, 2015). Additionally we plotted our results found during the SALTRACE campaign for pure Saharan dust and for the boundary layer.…”
Section: Impact On Aerosol Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…3 contrasts the corresponding intensive properties against each other. Such a data set is a valuable input for aerosol typing approaches and can be used for, e.g., data analysis algorithms of the new generation of space-borne lidars (Illingworth et al, 2015;Groß et al, 2015). A first collection of intensive properties (lidar ratio at 355 and 532 nm, Ångtröm exponents and particle depolarization ratio) was presented for different aerosol types by Müller et al (2007) obtained mainly by ground-based field campaigns including some of the very first Polly NET measurements in China.…”
Section: Summarizing Discussionmentioning
confidence: 99%
“…concentration-independent, optical properties but also on aerosol load, geographic location or altitude of occurrence. Such schemes have been developed in the context of the CALIPSO mission [3,4], derived from dedicated lidar field studies [5,6] or retrieved from passive remote-sensing observations [7].…”
Section: Aerosol Classification Schemesmentioning
confidence: 99%